Diseño e implementación de un sistema de monitoreo para la compañía de transportes Planeta Transplaneta S.A. utilizando tecnologías inalámbricas gps y gprs - Ojeda Capa, Edison Vinicio (2015)
In the present document it describes the process of the design and implementation of hardware and software of a monitoring system of bus stops, in the Transportation Company Planeta Transplaneta for the route Cutuglagua San Roque, in the Metropolitan District of Quito using wireless technologies: Global Positioning System (GPS) and General Packet Radio Service (GPRS). In order to control improper use of public transportation stops and optimize time on the distance traveled, this system used a GPS module it provides localization data of the transport unit, which are subsequently sent to a website designed exclusively for this system through GPRS technology. The communication and interaction of the mentioned systems, was performed through microcontroller Atmega164P. The data stored on the web server reflected the route made by unit of the Company, which were analyzed and evaluated, to establish a pattern of time used, behavior of travel and infractions committed by the driver. This parameters were used as indicators to improve the quality of service provided by the company. The proper functioning of the system determined that the rate of infringements committed is high, causing a delay in the time of realization of route, so this system is presented as a potential tool to controlling and punishing such contravention.